Optimization of Heat and Mass Exchange - Agnew, Brian; Tam, Ivan CK; Shi, Xiaojun (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue of Processes operates on the basis of a rigorous peer-review with a single-blind assessment and at least two independent reviewers, thereby ensuring a high quality final product. I would like to thank our reviewers, for providing the authors with constructive comments, and Editorial Board, for their professional advice that led to the final decision. I am sure that, in coming years, readers of this Special Issue will find the scientific manuscripts interesting and beneficial to their research.
English
Keywords: three-dimensional temperature field; n/a; forced convection; RNG k-? model; PIV measurements; water friction loss; flat plate; horizontal; optimization; casson fluid; finned tube; plate-fin heat sink; computational fluid dynamics (CFD); plate heat exchanger; partial heating; thermo-diffusion; HEN synthesis; Keller-Box technique; visualization experiment; ice-cream; modelling; computational intelligence techniques; canned motor; boiling; heat transfer; operating condition; vertical; phase change; flow distribution characteristics; scraped surface heat exchanger; heat flux; numerical simulation; aspect ratio; orientation; axisymmetric flow; CACRS; natural convection; MINLP; multi-slip; ice storage; viscosity; axial piston pump; crystallization; multiphase flow